Association Between Plasma Homocysteine Levels and Subclinical Hypothyroidism in Adult Subjects: A Meta-Analysis - Zhang, Shou-Fa; Li, Li-Zhi; Zhang, Wei; Guo, Jin-Rong; Liu, Fang-Fang; Ma, Kai; Chen, Shao-Hua; Zhang, Ya-Qing (Hormone and Metabolic Research, 2020)
Increased plasma homocysteine (Hcy) levels have been widely documented in patients with overt hypothyroidism; however, the significance of Hcy level changes in patients with subclinical hypothyroidism (SCH) remains controversial. The aim of this meta-analysis was to determine the Hcy status in patients with SCH compared with euthyroid subjects. We searched PubMed, Embase, and Cochrane Library databases prior to December 2019 to identify eligible studies and assessed the quality of selected studies using the Newcastle-Ottawa Quality Assessment Scale. Publication bias was evaluated by Begg’s test and Egger’s test. Meta-regression analysis was conducted to investigate the source of heterogeneity. A likely source of heterogeneity was the year of the study. All statistical analyses were performed with RevMan 5.3 and Stata 12.0 software. Our meta-analysis of twelve observational studies with 684 patients showed that those with SCH aged between 18 and 65 years old were associated with a slightly increased plasma Hcy level compared with euthyroid controls. The pooled result of the weighted mean difference (WMD) of increased tHcy levels was 1.16 μmol/l (95% CI: 0.51, 1.82; p=0.0005). The Hcy level in patients with SCH aged between 18 and 65 years old is significantly increased compared to euthyroid controls.
Keywords: Subclinical hypothyroidism; hyperhomocysteinemia; cardiovascular disease; meta-analysis